2009
DOI: 10.1007/s11661-008-9710-3
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Lotus-Type Porous Al-Si Alloys Using the Continuous Casting Technique

Abstract: Lotus-type porous 8,12,14, and 18 wt pct) alloys were fabricated using the continuous casting technique under a hydrogen gas pressure of 0.1 MPa at various transference velocities, and the effects of the silicon content level and transference velocity on the pore morphology and porosity were investigated. Both the porosity and the average pore diameter increase as the silicon content level increases and decrease as the transference velocity increases. In particular, the velocity dependence is obviously exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
0
24
1
1
Order By: Relevance
“…The growth of pores is interrupted by the surrounding primary -dendrites, when the volume fraction of eutectic phase is small according to the results of fabrication of lotus-type porous Al-Si alloys. 7) In Al-4 mass% Si and Al-8 mass% Si with a small volume fraction of eutectic phases, the morphologies and direction of pores were influenced by the surrounding primary -dendrites. On the other hand, in Al-Si alloys with a Si-content of 12, 14, and 18 mass% with a large volume fraction of eutectic phases, the pores grew in the solidification direction and were in a cylindrical shape.…”
Section: Pore Morphology and Solidification Conditionsmentioning
confidence: 94%
See 1 more Smart Citation
“…The growth of pores is interrupted by the surrounding primary -dendrites, when the volume fraction of eutectic phase is small according to the results of fabrication of lotus-type porous Al-Si alloys. 7) In Al-4 mass% Si and Al-8 mass% Si with a small volume fraction of eutectic phases, the morphologies and direction of pores were influenced by the surrounding primary -dendrites. On the other hand, in Al-Si alloys with a Si-content of 12, 14, and 18 mass% with a large volume fraction of eutectic phases, the pores grew in the solidification direction and were in a cylindrical shape.…”
Section: Pore Morphology and Solidification Conditionsmentioning
confidence: 94%
“…5,6) The thermal decomposition method was developed by Nakajima and Ide in order to fabricate lotus-type porous metals without explosive gas and high pressure chamber. 5) Until now several kinds of lotus aluminum alloys have already been fabricated with hypo-eutectic Al-Si alloys 7) and hypo-eutectic Al-Cu alloy 8) by continuous casting technique in hydrogen atmosphere of 0.1 MPa. These results showed that pores were formed in the eutectic region among several primary -dendrites by the solubility gap of hydrogen between liquid and solid phases, and then grew in the direction of growth of the columnar primary -dendrites.…”
Section: Introductionmentioning
confidence: 99%
“…Table I is a compilation of these works. [5][6][7][8][9][10][11][12][13][14][15] Although aluminum alloys have high porosities, especially alloys with Si [15] and Fe, [12] none of the previous works produced porous aluminum with directional pores and a high porosity; the porosity is limited to 5 pct at most.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to increase porosity and to clarify the pore formation mechanism in lotus aluminum, it is reasonable to consider the competitive growth between directional pores and solid metal because the hydrogen flux is related to the solidification conditions. Several experimental investigations have examined the effects of partial pressure and solidification velocity on the porosity and pore size in metals (copper, [15,21] stainless steel, [22] and magnesium [23] ) to evaluate the porosity and pore size from the solidification processing parameters. On the other hand, pore growth in lotus metals has been theoretically evaluated from the viewpoint of competitive growth between directional pores and solid metal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation